2019
DOI: 10.2147/cia.s189040
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nutritional status and frailty in hospitalized older patients

Abstract: ObjectiveThe definition of frailty still lacks quantitative biomarkers. This study aimed to investigate the relationship between nutrition-related biomarkers and frailty in hospitalized older patients.Materials and methodsThis is a cross-sectional study including 380 hospitalized older patients. The patients were categorized as nonfrail (n=140), prefrail (n=81), and frail (n=159) by the criteria of frailty phenotype. The nutritional status was assessed using the mini nutritional assessment-short form (MNA-SF),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 28 publications
5
43
0
1
Order By: Relevance
“…Previous studies showed that there was a close relationship between nutritional status and frailty. 31 Our study also found lower albumin which reflected nutritional status was independently associated with frailty. D-dimer is an important clinical assay for the detection of active coagulation and fibrinolysis.…”
Section: Associated Risk Factors Of Frailtysupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies showed that there was a close relationship between nutritional status and frailty. 31 Our study also found lower albumin which reflected nutritional status was independently associated with frailty. D-dimer is an important clinical assay for the detection of active coagulation and fibrinolysis.…”
Section: Associated Risk Factors Of Frailtysupporting
confidence: 69%
“…The overall prevalence of frailty in our study was consistent with previous published results which showed that 18% to 54% of elderly inpatients were frail among different regions in China. [15][16][17][18][19][20]31 However, no published results showed the data of frailty from different wards simultaneously, mostly only focusing on the department of geriatrics or only one type of disease. Our results revealed that non-surgical wards had the highest incidence of frailty and longest hospital length among the cardiac ward and surgical wards.…”
Section: Prevalence Of Frailty In Elderly Hospitalized Patientsmentioning
confidence: 99%
“…Increased Hb levels may be a protective factor for decreasing hospitalization rates and duration. Importantly, Hb could be an early indicator of the nutritional status of hospitalized elderly patients (30). The home care system in Taiwan made great efforts to advocate the avoidance of frequent admissions and provided phone consultation as required (13).…”
Section: Discussionmentioning
confidence: 99%
“…Higher Hb levels seemed to be a protective factor for decreasing hospitalization rates and duration of stay. Importantly, Hb could be an early indicator of nutritional status, related to hospitalized elderly patients (27). The home care system in my country made great efforts to advocate the avoidance of frequent admissions and provided phone consultation when needed (13).…”
Section: Discussionmentioning
confidence: 99%